Assessment of Morus alba (Mulberry) leaves extract for anti-convulsant property in rats - Rayam, Sriharsha; Kudagi, B. L.; M., Umer Sufyan; Buchineni, Madhavulu; Pathapati, Rama Mohan (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The mulberry tree, a plant of the family Moraceae and the genus Morus, has been widely cultivated to feed silkworms. Various parts of Morus alba linn used as an Anti-inflammatory, hypoglycemic, cardioprotective, hepatoprotective, free radical scavenging activity and neuroprotective agent. The plant contains flavonoids, moranoline, albanol, morusin coumarine, and stilbene, which have. In this study, anticonvulsant property of Morus alba leaves extract (MAE) was evaluated by using MES and PTZ induced convulsion in rats. Methods: Effects of MAE were evaluated in experimental models of electro convulsions, maximal electro shock (MES) and chemoconvulsion induced by pentylenetetrazole (PTZ) in rats (n=6), which were treated intraperitonially with doses of 100, 200 and 400mg/kg. Results: The duration of tonic hind limb extension (seconds) with MAE in MES induced convulsions at dose of 100, 200, 400 mg/kg is 8.33±1.21, 6.83±1.16 & 3.16±0.98 respectively. In the dose of 400 mg/kg of MAE showed highly significant results by reducing the duration of tonic hind limb extension in MES induced convulsions. And onset of jerky movements (seconds) with MAE in PTZ induced convulsions at dose of 100, 200, 400mg/kg is 157.83±8.99, 195.66±17.02 and 295.50±21.10 respectively. In the dose of 400mg/kg of MAE showed highly significant results by delaying the onset of convulsions. Conclusions: Results indicate that the MAE have anticonvulsant effects in MES induced convulsions and in PTZ induced convulsions.